Strain-volume loops for assessment of diastolic function in hypertrophic cardiomyopathy. (4th February 2022) - Pagourelias, E; Boulmpou, A; Alexandridis, G; Tsarouchas, A; Mouselimis, D; Bakogiannis, K; Karamanolis, A; Vergopoulos, S; Tsavousoglou, C; Antoniadis, A; Fragakis, N; Papadopoulos, CE; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Diastolic function assessment in patients with hypertrophic hearts and preserved ejection fraction (EF) is a rather challenging task, necessitating the introduction of new parameters. Strain-volume loops (SVLs), based on simultaneous frame-by-frame strain and volume changes' recordings acquired by means of three-dimensional (3D) speckle tracking imaging, is an innovative tool which has been applied in various substrates. The ability of SVLs to assess diastolic function in hypertrophic cardiomyopathy (HCM) has not been investigated until now. Purpose: Aim of this study was to investigate potential correlations between SVLs, traditional diastolic function indices and phenotypic features of HCM (thickness, obstruction and fibrosis) that may also reflect myocardial "stiffness". Methods:  We included 40 HCM patients (54.1 ± 14.3 years, 82.5% male, maximum wall thickness 19.3 ± 4.8mm) who have consecutively undergone 3D-speckle tracking echocardiography (panel A) and cardiovascular magnetic resonance (CMR) with late gadolinium enhancement (LGE). Values of 3D strain were plotted vs. volume for each frame to build an SVL. Peak of radial, longitudinal and circumferential systolic strain (Rsp, Lsp, and Csp, respectively), systolic slopes of the loops (RsSl, LsSl, CsSl), strain to end-diastolic volume (EDV) ratios (Rs/V, Ls/V, Cs/V) as well as the extent of systolic-diastolic uncoupling (difference between systolic and diastolic strain for the same volume) were computed for the analysis. Left atrial volume index (LAVI), E/E' and tricuspid regurgitation velocity (TRvel) were measured to define diastolic dysfunction (DD) stage. Burden of fibrosis was evaluated by LGE extent in CMR slices. Results:  All HCM patients had preserved EF (60.5 ± 5, 7%), while 16 (40%) had LV outflow tract obstruction (LVOTO > 30 mm Hg at rest). Mean LV mass index was 78.9 ± 14.5 g (evaluated by 3D echocardiography). LGE was observed in 23 patients (57.5%) occupying 5.2 ± 4.5% of LV mass. Concerning SVLs the following values were recorded for radial (Rsp 30.8 ± 9.8%, RsSl 0.4 ± 0.13 and Rs/V 0.25 ± 0.09), longitudinal (Lsp -9.4 ± 3.7%, LsSl 0.12 ± 0.06 and Ls/V 0.08 ± 0.04) and circumferential deformation (Csp -14.2 ± 3.5%, CsSl 0.18 ± 0.05 and Cs/V 0.11 ± 0.03). Traditional isolated diastolic indices (E/E', LAVI, TRvel and DD stage) did not present significant correlations with SVL parameters or HCM phenotypic features. However, potentially "stiffer" hearts (combination of increased LVMI and fibrosis) presented a leftward transition of longitudinal SVLs, which also became wider (greater uncoupling) (panel B). Conclusions: Traditional diastolic indices show modest only correlations with SVLs or HCM phenotypic characteristics, necessitating new approaches to DD of HCM patients. SVLs seem to be a promising-innovative tool for indirect assessment of myocardial "stiffness" and diastolic function.